2010
DOI: 10.1128/mcb.00624-10
|View full text |Cite|
|
Sign up to set email alerts
|

Analysis of CUGBP1 Targets Identifies GU-Repeat Sequences That Mediate Rapid mRNA Decay

Abstract: CUG-repeat binding protein 1 (CUGBP1) mediates selective mRNA decay by binding to GU-rich elements (GREs) containing the sequence UGUUUGUUUGU found in the 3 untranslated region (UTR) of short-lived transcripts. We used an anti-CUGBP1 antibody to immunoprecipitate CUGBP1 from HeLa cytoplasmic extracts and analyzed the associated transcripts using oligonucleotide microarrays. We identified 613 putative mRNA targets of CUGBP1 and found that the UGUUUGUUUGU GRE sequence and a GU-repeat sequence were both highly en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
148
1
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 111 publications
(162 citation statements)
references
References 31 publications
12
148
1
1
Order By: Relevance
“…We found that several GRE-like sequences were the most highly enriched motifs (Table 2, left). These results corroborated previous reports showing that both (UGUU) n motifs and (UG) n motifs were enriched in the 3Ј-UTRs of CUGBP1 target transcripts (13,25). Additionally, the 3Ј-UTRs from CUGBP1 target transcripts were submitted to a BioProspector motif search (26) to evaluate enriched sequences.…”
Section: Gres Are Enriched In Cugbp1 Target Transcripts In Primary Husupporting
confidence: 77%
See 4 more Smart Citations
“…We found that several GRE-like sequences were the most highly enriched motifs (Table 2, left). These results corroborated previous reports showing that both (UGUU) n motifs and (UG) n motifs were enriched in the 3Ј-UTRs of CUGBP1 target transcripts (13,25). Additionally, the 3Ј-UTRs from CUGBP1 target transcripts were submitted to a BioProspector motif search (26) to evaluate enriched sequences.…”
Section: Gres Are Enriched In Cugbp1 Target Transcripts In Primary Husupporting
confidence: 77%
“…RNA-IP and Microarray Analysis-Cytoplasmic extracts were prepared from resting and stimulated T cells, and RNA-IP reactions were performed as described previously, using antibodies targeting hemagglutinin (HA) (F7, Santa Cruz Biotechnology, Inc. (Santa Cruz, CA)), CUGBP1 (3B1, Santa Cruz Biotechnology, Inc.) or poly(A)-binding protein (PABP) (ImmunoQuest) (13). Three RNA-IP experiments were performed using resting or activated T cells isolated from three individual anonymous donors.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations